PENERAPAN MODEL TEAMS GAMES TOURNAMENT (TGT) BERBASIS MISI KELOMPOK UNTUK MENINGKATKAN KETERAMPILAN KOLABORASI SISWA KELAS 5 SDN SUKUN 3 - Adelia Vicky Vernanda; Farida Nur Kumala (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Collaboration skills are one of the essential competencies that students need to develop in the twenty-first century. However, observations conducted in Grade V of SDN Sukun 3 indicated that students' collaboration skills were still relatively low. This condition was reflected in unequal participation during group discussions, limited communication among students, uneven task distribution, and the dominance of certain group members in completing learning activities. This study aimed to improve students' collaboration skills through the implementation of a Mission-Based Teams Games Tournament (TGT) learning model. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The study involved Grade V students of SDN Sukun 3 and was conducted in two cycles. Data were collected through collaboration observation sheets, field notes, and documentation, then analyzed using descriptive quantitative and qualitative techniques. The findings revealed that the implementation of the Mission-Based Teams Games Tournament learning model successfully improved students' collaboration skills. Students demonstrated better cooperation, communication, responsibility, respect for peers' opinions, and active participation in completing group tasks. Therefore, integrating group missions into the Teams Games Tournament model can create a more engaging, interactive, and collaborative learning environment in elementary school classrooms.